Study of some water chemical variables, sodium and arsenic concentration in a section of the Upper-Tisza Region - Türk, Gábor; Prokisch, József (JOURNAL OF LANDSCAPE ECOLOGY, 2014)
Occasionally high arsenic concentrations of groundwater are the result of the natural geochemical processes in contrast to anthropogenic contaminations. Nowadays, arsenic is the most considerable natural contamination in groundwater and its reduction belongs to the great challenge of water management in the 21st century. The catchment area of the Main Canal Lónyay is qualified as an area potentially polluted by arsenic as the result of geological processes. However, this hazard endangers not only the residents living in the region of Nyírség, but also it appears in other areas of the Great Hungarian Plain. The floor-level of the main channel incises to the ground-water level in some points of the catchment area due to its structural character. In consequence, substantial amount of ground-water can get into certain mainstreams by which arsenic can also get into the surface water bodies. In this area there’s no remarkable industrial institution which could mean further contamination to water bodies. However, it can cause pollution in leachate collected from certain landfills. We revealed a power-law relationship in the correlation of arsenic and runoff in both cases of surface water bodies (Tisza and Main Canal Lónyay). Runoff is increased and concentration is precipitously decreased by the increasing amount of precipitation. The values, measured below the firth at sample location, were exceeded the values of upper and lower river sections in both cases of arsenic and nutrient turnover. We experienced significant differences among sample locations of Tisza in point of every measured component. Arsenic concentration was below the threshold level in all samples.